CRIMINOLOGICAL CHARACTERIZATION OF OFFICIALS OF LEGAL ENTITIES UNDER PUBLIC LAW WHO COMMIT CORRUPTION GRIMES IN OFFICIAL ACTIVITIES (Bulletin of criminological association of Ukraine, 2024)
Based on official statistical sources, the article presents a long-term criminological analysis (2016-2023) of officials of legal entities under public law who commit corruption crimes in the course of their official activities. The analysis identifies specific characteristics of the individuals under study, the main findings of which are: a higher proportion of women (in relation to the total number of crimes and convictions) (14.6% among those detected and 12.3% among those convicted); a dominant proportion of persons aged between 29 and 54 (over 70%) in the structure of those detected and those convicted; high level of education (persons with a university degree account for 89. 6%); the largest employment categories among these individuals are law enforcement officers (48.5%), civil servants (21.5%), and local government officials (10.4%); the recidivism rate is extremely low (1.7%). The distribution of identified individuals by type of crime committed reveals that 17.8% are involved in abuse of power or official position, while 82.2% are implicated in accepting an offer or promise, or receiving of an undue advantage. This study has both theoretical and practical significance, as it contributes to the further typology of such individuals and to the development of an appropriate system of specific criminal preventive measures.
Keywords: officials; legal entities under public law; corruption crimes; sphere of official activities; personality of offender; crime; crime prevention; criminological signs; criminological characterization; criminal offenses; Criminal Code of Ukraine